P045 Oncostatin M induces strong fibrotic and chemokine responses from primary colonic subepithelial myofibroblasts. (27th May 2021) - Kokkotis, G; Tarapatzi, G; Drygiannakis, I; Filidou, E; Kandilogiannakis, L; Arvanitidis, K; Valatas, V; Koutroubakis, I; Vradelis, S; Kolios, G; Bamias, G
Abstract: Background: Oncostatin M (OSM) may play an important role in Inflammatory Bowel Disease (IBD) pathogenesis. Specifically, both OSM and its receptor are upregulated in inflamed colonic regions of IBD patients, and high OSM expression has been associated with failure to respond to anti-TNF therapy. Our aim was to investigate the effect of OSM in fibrotic factors and chemokine expression on primary colonic subepithelial myofibroblasts (SEMFs) from healthy individuals (HI). Methods: Primary SEMFs were isolated from endoscopically-obtained colonic biopsies from HI. SEMFs were stimulated with 1, 10, or 100ng/ml OSM for 6 hours, with or without pre-stimulation with 5ng/ml IL-1α plus 50ng/ml TNF-α for 24h. Total RNA was collected and mRNA transcripts for collagen type I, type III, fibronectin, and the chemokines CCL2, CXCL9, CXCL10 and CXCL11 were measured by reverse transcription quantitative PCR. Results: Unstimulated SEMFs had a basal expression of collagen type I, III, fibronectin, CCL2, CXCL9, CXCL10 and CXCL11. OSM stimulation augmented chemokine mRNA expression in a dose-dependent manner (Table 1 ) but had no effect on fibrotic factors expression. Pre-stimulation of myofibroblasts with TNF-α and IL-1α resulted in augmented expression of collagens I and III and fibronectin, in addition to further increases in chemokine expression in response to subsequent stimulation by OSM (Table 2 ). Conclusion: Our results show that stimulation with OSM induces fibrotic and chemokine responses by SEMFs. Our findings further support the hypothesis that SEMFs may play a key role in regulating chronic intestinal inflammation and response to biological therapy.